Two examples of high-efficient and green biotransformations - D. Romano; L. Tamborini; A. Pinto; P. Zambelli; P. Conti; F. Molinari (2012)
a) Lipase-catalysed resolution and in-line purification of racemic flurbiprofen in a continuous-flow reactor1 A fast, efficient and automated method to obtain both enantiomers of flurbiprofen is reported. Kinetic resolution of (R,S)-flurbiprofen using lipase B from Candida antarctica (Novozym 435®) has been performed in a flow-chemistry reactor and results were compared to the traditional batch process. We observed a significant reduction of the reaction time from 6 h (in batch) to 15–60 min in flow, depending on the desired degree of conversion. The process was implemented by adding an in-line purification step, consisting in a separation of products from substrates thanks to a catch and release protocol. Worth noting, after the initial set-up of the system, the present protocol allows the obtainment and easy recovery of both (S)-flurbiprofen and (R)-flurbiprofen butyl ester with an enantiomeric excess ≥90% and a chemical purity >98%, by simply modulating the reaction conditions (temperature and residence time). The process was scaled up to 80 mM concentration of the starting solution and enzyme performances were assessed upon several hours of continuous work b) One-pot chemoenzymatic synthesis of aldoximes from primary alcohols in water2 Oximes are useful chemical compounds widely used in different industrial fields: pharmaceutical (as anti-tumoral, antimicrobial, antioxidant, anticonvulsant and antiviral), flavour and fragrances (as corresponding stable-compounds of intrinsic instable and volatile aldehydes), materials (e.g. as precursor of caprolactam), food (Perillartine, the oxime of perillaldehyde is used as an artificial sweetener in Japan, as it is 2000 times sweeter than sucrose) and synthetic chemistry (as precursors in many reactions). We have established an easy and efficient alternative to previous heavy metal-based solutions for the one-pot preparation of aldoximes directly from alcohols, combining the oxidation of alcohols to aldehydes by dehydrogenases of acetic acid bacteria and the instant ...